Effect of density and weight of load on the energy cost of carrying loads by donkeys and ponies - Pearson, R.A.; Dijkman, J.T.; Krecek, R.C.; Wright, P. (Edinburg (South Africa), 1998)
Sumario (En)
Ilus.; 32 ref.
Keywords: ANIMALES DE TRABAJO; TRACCION ANIMAL; CARGA GANADERA; PESO; GENERACION DE ENERGIA; ASNO